Peran Pondok Tri Bhakti At-Taqwa dalam Meningkatkan Sikap Religius Peserta Didik di SMP Qur’an Tri Bhakti At-Taqwa Lampung Timur - M.Fathul Munip; Irhamudin; Adi Wijaya (CV. Creative Tugu Pena, 2024)
The problem often occurs in connection with moral cases in the surrounding environment due to the increasingly sophisticated social media. There is a phenomenon of a decline in a person's character, for example, Lack of Character Education, lack of attention and supervision of parents in accompanying their children in using technology and social media can cause them to be trapped in bad behavior. From time to time, Islamic boarding schools have played a very important role in the history of Islamic education in Indonesia. Islamic boarding schools themselves are a field in the habituation of religious attitudes that become religious culture can be built in three ways, namely: invitation, experience, and habituation. The researcher used a qualitative research method in this study, the researcher chose to use the type of field research with This study aims to explore more deeply how the role of Islamic boarding schools in cultivating religious attitudes, as well as identifying factors that influence differences in religious attitudes between students and non-students at SMP Qur'an Tri Bhakti At Taqwa Lampung Timur. After the researcher visited the Caretaker of the Islamic Boarding School, the Tri Bhakti At Taqwa Islamic Boarding School plays a central role in shaping the religious character of students through religious cultural activities held in the boarding school. Through this study, it is hoped that findings can be produced that can contribute to the development of religious education in Indonesia, especially in shaping the character of the younger generation who are more religious and have noble character.